Software quality evaluation through maintenance processes - Al-Badareen, Anas Bassam; Muda, Zaiton; A. Jabar, Marzanah; Din, Jamilah; Turaev, Sherzod (2010)
The software is always required to be developed and maintained a quality to the rapid progresses in industry, technology, economy, and other fields. Thus, software maintainability is the major activity in the software life cycle. This process bypass the cost required to develop new software product. However, software maintenance costs often total twice the original development cost in the lifetime of application software. Therefore, software maintainability is considered as one of the most important quality factor in software quality models. This study introduces a software maintenance process model that emphasizes the impact of the software quality on the maintenance and considers the quality of the modified software.